The Impact of Vertical Jump Exercise in the Postsynaptic Cleft in Wistar Rats - Rocha-Braga, Lara Caetano [UNESP]; Gomes, Isabella [UNESP]; Neto, Jurandyr Pimentel [UNESP]; Tomiate, André Neri [UNESP]; Camargo, Paula Oliveira [UNESP]; da Silva, José Roberto Rodrigues [UNESP]; Ciena, Adriano Polican [UNESP] (Edra SpA, 2024)
Background. Skeletal muscle tissue demonstrates remarkable adaptability responding to stimuli at the neuromuscular junction (NMJ) during activities like vertical jumping, an essential ability in sports. Research about these changes can offer insights into neuromuscular plasticity. Objective. The study aimed to explore the neuroplasticity of the postsynaptic cleft at the NMJ after vertical jump (VJ) training in twenty 90-day-old male Wistar rats, divided into Sedentary (S) and Jumper (J) groups. Methods. A combination of immunostaining and microscopy was used to analyze structural and functional changes at the NMJ. α-Bungarotoxin highlighted the postsynaptic components, while fluorescence microscopy detailed the tissue and NMJ structures. Statistical analyses, including the Mann-Whitney test and the Shapiro-Wilk test, were used to compare groups and test data normality, with a significance level of p < 0.05 to ensure the relevance of the results. Results. The morphometric analysis of the NMJ showed that the J group had a smaller postsynaptic cleft compared to the S group. There were no significant differences in dispersion, AChR area, endplate area, or endplate perimeter between the groups but lower values in J Group (p < 0.05). However, the AChR perimeter was significantly lower in the J group (p < 0.05). Additionally, the J group had fewer AChR clusters and a lower fragmentation index, both significantly different (p < 0.005). Conclusions. VJ training modifies the NMJ affecting the organization and morphology of the motor endplate. This underscores the role of physical exercise in neuromuscular remodeling and calls for further studies to understand the functional implications of these adaptations.
Keywords: exercise; neuromuscular junction; neuroplasticity vertical jump; α-bungarotoxin